[8]-gingerol e metilsulfonilmetano atenuam a lesão renal aguda induzida por Vancomicina em modelo Murino - Ferreira, Francisco Cleber Silva (2025)
Vancomycin (VCM) is a glycopeptide antibiotic commonly used against methicillin-resistant Gram-positive cocci and its use has been associated with Acute Kidney Injury (AKI), with an incidence of between 5% and 43% of patients, making it an important clinical problem. The mechanism of nephrotoxicity is not well understood, but studies suggest that oxidative stress is one of the mechanisms responsible for its pathophysiology, and that the use of antioxidants could prevent kidney damage. From this perspective, the compound [8]-gingerol (8G), a bioactive substance from ginger (Zingiber officinale), has antioxidant and anti-inflammatory properties. The compound methylsulfonylmethane (MSM) is a natural organosulfur that has been widely used as a dietary supplement, showing protective effects against various disorders through its anti-inflammatory and antioxidant properties, both compounds could exert a renoprotective effect. This study aims to investigate the nephroprotective potential of the compounds 8G and MSM in VCM-induced AKI. The protocols were carried out in accordance with the rules of the National Council for Animal Control and Experimentation (CONCEA) and approved by the Animal Use Ethics Committee (CEUA)-UFC under protocol number 9270120318. Male Swiss mice were used. Firstly, the time of induction (3, 5 and 7 days) of AKI by VCM (400mg/kg/day i.p.) was characterized. In terms of nephrotoxicity, an induction time of 7 days was chosen. For the experimental block treatment with the compounds 8G and MSM, the animals were divided into 5 groups (n=6-8): control (CTR), Lesion (VCM) and the treatment groups 8G (VCM+8G) and MSM (M5+VCM and M7+VCM) administered orally (gavage) at a dose of 20mg/kg for 8G and the doses 500mg/kg and 750mg/kg for MSM, administered twice a day for the same period of time chosen for AKI induction. After the experimental period of VCM induction, 24-hour urine samples were collected for biochemical tests, after which the animals were euthanized to collect plasma samples to measure plasma urea and creatinine. The kidneys were collected, weighed and used for histopathological analysis, myeloperoxidase (MPO) activity and gene transcription of inflammatory mediators, antioxidants and early biomarkers of kidney damage by real-time polymerase chain reaction (qPCR). The induction of AKI by VCM significantly altered the parameters of kidney weight, plasma creatinine and urea, urinary protein and volume, MPO, GSH, KIM-1, NGAL, IL-1β, TNFα, CXCL-1, NFκBp65, HO-1, SOD-1, SIRT-1,STAT-3, JNK and histopathological parameters (P<0.05). Compound 8G significantly altered kidney weight, plasma creatinine and urea, urinary protein and volume, NGAL, TNFα, NFκBp65, IL-1β, STAT-3, JNK and increased the expression of SOD-1 and SIRT-1 (P<0.05). MSM at a dose of 1g/kg/day significantly (P<0.05) reduced plasma creatinine and urea, MPO, NGAL, IL-1β, CXCL-1 and STAT-3. MSM at a dose of 1.5g/kg/day was the group that showed the best results, reflected in the findings of kidney weight, serum creatinine and urea, urinary protein and volume, MPO, KIM-1, NGAL, IL-1β, TNFα, CXCL-1, NFκBp65 and STAT-3. Improvement in the histological parameter of border loss was observed for both compounds. It is concluded that the present study established a model of VCM-induced AKI and that the compounds 8G and MSM were able to protect the renal morphofunctional dysfunction triggered by VCM, through anti-inflammatory and antioxidant actions, possibly through the suppression of NFkBp65/STAT-3/JNK activity and the involvement of SIRT-1.